Meningkatkan Keterlibatan RT/RW dalam Penggunaan Aplikasi Pelumas untuk Pelayanan Desa Karangsatria - Mahendra, Baramulih; Wijaya, Bintang; Wulandari, Anisya; Pertiwi Alawiah, Evita; Faishal Rafi, Ahmad; Pangestu, Angsal; Ihawan Ariyandi, Fadjar; Nabil Praditiyanto, Hikmal; Ramdhani Mahbub, Asep (VINICHO MEDIA PUBLISINDO, 2024)
Community service through the Community Service Program (KKN) is a form of student contribution to addressing issues in society. This study aims to examine the role of KKN in increasing the involvement of RT (Neighborhood Associations) and RW (Community Associations) in the use of the Pelumas (Public Service) application in Karang Satria Village. The methods used in this study include observation and interviews. KKN students participated in activities to socialize and train the use of the Pelumas application to village officials and local residents. The results showed that through KKN, the involvement of RT and RW in using the Pelumas application significantly increased. The community began to understand the importance of technology in improving the efficiency of village services. RT and RW also demonstrated increased knowledge and ability in using the Pelumas application for various administrative and public service purposes. These findings highlight the importance of collaboration between students, village officials, and the community in leveraging technology for sustainable development.